Nitrogen levels through fertirrigation and plant density on melon crop in a Vertisol - Costa, Nivaldo Duarte; Pinto, José Maria; Brito, Luiza Teixeira de Lima; Soares, José Monteiro (Pesquisa Agropecuaria Brasileira, 2000)
This study consisted of one experiment with melon (Cucumis melo L.), carried out in a Vertisol in Juazeiro, BA, Brazil, in 1995, with the objective of evaluating the effects of nitrogen levels through fertirrigation and plant density on fruit yield and quality. The N levels were 0, 80, 130 and 180 kg/ha, combined with row spacings of 2.0 and 1.8 m and 0.20 m between plants within the row, with one or two plants/hole. The source of N was urea applied daily up to 42 days after germination, through drip irrigation. All treatments had a uniform fertilization of 120 kg/ha of P2O5 and 120 kg/ha of K2O. No significant difference was caused by spacing between rows in the studied variables. Eighty kg/ha of N combined with one plant per hole gave a yield of 34.07 ton/ha, being 55,7% of fruit allocated to inside market, not significantly lower than those obtained with the highest N levels in any combination. This same N level gave fruits with 10.22o Brix, significantly higher than the treatment without N and not significantly lower than the other levels. In order to get high number of good fruit for out side market it was necessary to elevate the density to two plants per hole and N level to 130 or 180 kg/ha. Mean weight of fruits increased from 1.008 to 1.705 kg with the increase in the levels of N and the decrease in plant density of two plants per hole to one plant per hole.